Sistem Pendukung Keputusan Penerangan Ruangan Berbasis IoT Menggunakan Protokol MQTT dan Fuzzy Tsukamoto - Ahmad Fauzan Hakim; Wirarama Wedhaswara; Ahmad Zafrullah Mardiansyah (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
Inappropriate use of a light bulb in light conditions in the room causes electricity to go to waste. To conserve electricity and keep the lights from breaking quickly, it needs to be done to measure the condition of the light around the lamp. For that it requires a decision-making system of the lighting room based on the Internet of things and using MQTT protocol and fuzzy tsukamoto logic methods. The MQTT protocol used is CloudMQTT to store data or be called a broker. CloudMQTT has 4 important instance info, that is server, user, password, and port. 4. That instance info is used to connect the application program with the broker in order for the system to subscribe and publish from broker to application. For fuzzy tsukamoto combination of rules built up from the three functions of membership, that is the intensity of light, time, and the condition of the light. A combination of rules from two variables is light intensity and time generates 20 combinations of rules. Deffuzification on fuzzy tsukamoto earned by taking a centralized average.